LEARNING MULTIMEDIA BASED INFORMATION SERVICES - Hidayati, Awik -; Ismail, Ismail (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2018)
This study was aimed at developing the media in order to support learning information service activities carried out by teacher guidance and counseling. The main results of the study are multimedia products that are expected to become learning information service media to support the improvement of learning achievement seen through indicators of learning habits. The research method used in this research was research and development. The research population was junior high school students in Sukoharjo regency. The sampling was carried out using random sampling techniques for preliminary studies. The data were collected through interviews and observations. Data analysis technique used in this study was descriptive qualitative data analysis for the implementation of information services and the feasibility of multimedia-based learning information service media. The results show that first, the use of multimedia in learning information services has not been implemented by the Counseling Guidance teacher, so the service was monotonous and less creative. Second, the creation of multimedia-based learning information services has been through the feasibility test of practitioners and experts in the field of multimedia as well as the field of Guidance and Counseling. Third, the results of making multimedia-based learning information service media are feasible to be used by teachers. LAYANAN INFORMASI BELAJAR BERBASIS MULTIMEDIA Abstrak Penelitian ini bertujuan pada pengembangan media dalam rangka mendukung kegiatan layanan informasi belajar yang dilaksanakan oleh guru bimbingan dan konseling. Hasil utama penelitian adalah produk multimedia yang diharapkan dapat menjadi media layanan informasi belajar untuk mendukung peningkatan prestasi belajar dilihat melalui indikator kebiasaan belajar. Metode penelitian yang digunakan adalah penelitian dan pengembangan produk. Populasi penelitian yaitu SMP di Kabupaten Sukoharjo. Sampling dilakukan menggunakan teknik random sampling untuk studi pendahuluan. Pengumpulan data melalui wawancara dan observasi. Analisis data menggunakan analisis data kualitatif deskriptif untuk pelaksanaan layanan informasi dan kelayakan media layanan informasi belajar yang berbasis multimedia. Hasil penelitian menunjukkan sebagai berikut. Pertama, penggunaan multimedia dalam layanan informasi belajar belum dilaksanakan oleh guru Bimbingan Konseling sehingga pelayanan bersifat monoton dan kurang kreatif. Kedua, pembuatan layanan informasi belajar berbasis multimedia telah melalui uji kelayakan dari praktisi dan ahli di bidang multimedia maupun bidang Bimbingan dan Konseling, Ketiga, hasil pembuatan media layanan informasi belajar berbasis multimedia layak digunakan oleh guru Bimbingan Konseling.